2000
DOI: 10.1074/jbc.m007399200
|View full text |Cite
|
Sign up to set email alerts
|

Heparan/Chondroitin Sulfate Biosynthesis

Abstract: Human ␤1,3-glucuronyltransferase I (GlcAT-I) is a central enzyme in the initial steps of proteoglycan synthesis. GlcAT-I transfers a glucuronic acid moiety from the uridine diphosphate-glucuronic acid (UDP-GlcUA) to the common linkage region trisaccharide Gal␤1-3Gal␤1-4Xyl covalently bound to a Ser residue at the glycosaminylglycan attachment site of proteoglycans. We have now determined the crystal structure of GlcAT-1 at 2.3 Å in the presence of the donor substrate product UDP, the catalytic Mn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(84 citation statements)
references
References 29 publications
(17 reference statements)
4
80
0
Order By: Relevance
“…In fact, we have observed that the synthetic phosphorylated trisaccharideserine, Gal-Gal-Xyl(2-O-phosphate)-Ser, served as a better acceptor substrate than the unmodified counterpart for recombinant human GlcUA transferase I. 2 The acceptor recognition by a crystallized form of this GlcUA transferase I has recently been demonstrated by x-ray crystallography (55), and it has further been revealed that the crystallized enzyme specifically recognized the 6-O-sulfate group on the Gal(I) residue adjacent to the Xyl residue, 2 although it remains to be determined whether the phosphate on the Xyl and/or the 4-O-sulfate group on the Gal(II) residue can also be recognized by the crystallized enzyme. These findings suggest that the phosphorylation of the Xyl residue and sulfation of the Gal residues may be required for efficient elongation and maturation of the linkage region tetrasaccharide as prerequisites for the assembly of GAG chains.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have observed that the synthetic phosphorylated trisaccharideserine, Gal-Gal-Xyl(2-O-phosphate)-Ser, served as a better acceptor substrate than the unmodified counterpart for recombinant human GlcUA transferase I. 2 The acceptor recognition by a crystallized form of this GlcUA transferase I has recently been demonstrated by x-ray crystallography (55), and it has further been revealed that the crystallized enzyme specifically recognized the 6-O-sulfate group on the Gal(I) residue adjacent to the Xyl residue, 2 although it remains to be determined whether the phosphate on the Xyl and/or the 4-O-sulfate group on the Gal(II) residue can also be recognized by the crystallized enzyme. These findings suggest that the phosphorylation of the Xyl residue and sulfation of the Gal residues may be required for efficient elongation and maturation of the linkage region tetrasaccharide as prerequisites for the assembly of GAG chains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DVD (motif ii) participates in coordination of Mn ϩϩ , the small amino acids (GG) within motif iii allow the donor sugar to fit deep into the pocket, and an acidic amino acid within motif iv is proposed to make contact with the sugar acceptor and to participate in nucleophilic attack on it. Similarly, in the crystallographic structures of human GlcAT-I with its substrates (26,27), DDD (motif ii) interacts with UDP and Mn ϩϩ , and the E within motif iv interacts with the acceptor substrate and is proposed to participate directly in catalysis. Indeed, even though bovine ␤4GalT1 and human GlcAT-I exhibit no significant primary sequence similarity, when the locations of conserved motifs ii, iii, and iv are mapped onto their crystallographic structures, it is evident that the spatial relationships of these motifs to each other and to the substrate binding pocket are similar (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…: 919-541-2404; Fax: 919-541-0696; E-mail: negishi@niehs.nih.gov. 1 The abbreviations used are: GlcAT-I, ␤1,3-glucuronyltransferase; NDST, N-deacetylase/N-sulfotransferase; MES, 4-morpholineethanesulfonic acid; MME-PEG-2000, monomethyl ether polyethylene glycol 2000. 100 mM MES, pH 6.0, 10 mM MnCl 2 , 10 mM UDP-GlcUA, and 10% ethylene glycol.…”
Section: Methodsmentioning
confidence: 99%
“…Protein of the recombinant human GlcAT-I catalytic domain was cloned, expressed, and purified as previously described (1). Crystals of the enzyme were obtained by the vapor diffusion hanging drop method.…”
Section: Methodsmentioning
confidence: 99%